Parthenolide inhibits pro-inflammatory cytokine production and exhibits protective effects on progression of collagen-induced arthritis in a rat model. (May 2015) - Liu, Q; Zhao, J; Tan, R; Zhou, H; Lin, Z; Zheng, M; Romas, E; Xu, J; Sims, NA
<x xml:space="preserve">Abstract</x> Objectives: Progressive destruction of synovial joint cartilage and bone occurs in pathological conditions such as rheumatoid arthritis (RA) because of the overproduction of pro-inflammatory cytokines and activation of nuclear factor kappa B (NF-κB). Through the screening of NF-κB inhibitors by a luciferase reporter gene assay, we identified parthenolide (PAR) as the most potent NF-κB inhibitor, among several PAR analogue compounds. This study was undertaken to determine whether PAR inhibits pro-inflammatory cytokine production, cartilage degradation, and inflammatory arthritis. Method: The mRNA levels of pro-inflammatory cytokines were examined by real-time polymerase chain reaction (PCR). Proteoglycan content and release were determined by measuring glycosaminoglycan (GAG) levels using the dimethylmethylene blue (DMMB) dye-binding assay. The potential role of PAR in treatment of arthritis was studied using a collagen-induced arthritis (CIA) model. Results: We established that PAR, as a prototype compound, suppressed lipopolysaccharide (LPS)- and tumour necrosis factor (TNF)-α-induced increases in matrix metalloproteinase (MMP)-1, MMP-3, inducible nitric oxide synthase (iNOS), and interleukin (IL)-1β mRNA in chondrocytes. In addition, PAR prevented proteoglycan degradation triggered by pro-inflammatory cytokines. PAR treatment at the onset of CIA symptoms significantly reduced synovitis, inflammation, and pannus formation scores. Reduced synovial inflammation after PAR treatment was also reflected in significantly less bone erosion and cartilage damage. Conclusions: These data indicate a protective effect of PAR on the catabolic insults of pro-inflammatory cytokines on chondrocyte metabolism and GAG release in vitro and in CIA. PAR had anti-inflammatory and structure-modifying effects on experimental arthritis, suggesting that PAR may be useful as a potential alternative or adjunct therapy for inflammatory arthritis.